2016
DOI: 10.1039/c6nr00324a
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon light-sheet nanoscopy by fluorescence fluctuation correlation analysis

Abstract: Advances in light-sheet microscopy have enabled the fast three-dimensional (3D) imaging of live cells and bulk specimens with low photodamage and phototoxicity. Combining light-sheet illumination with super-resolution imaging is expected to resolve subcellular structures. Actually, such kind of super-resolution light-sheet microscopy was recently demonstrated using a single-molecule localization algorithm. However, the imaging depth and temporal resolution of this method are limited owing to the requirements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…As such it is of interest to look into nondiffracting, propagation-invariant beams. Various reports have emerged over the past few years evaluating Bessel beams (Andilla et al, 2017;Fahrbach, Gurchenkov, Alessandri, Nassoy, & Rohrbach, 2013b;Fahrbach & Rohrbach, 2010Gao, Shao, Chen, & Betzig, 2014;Gohn-Kreuz & Rohrbach, 2016;Zhang, Phipps, Goodwin, & Werner, 2016;Zhao et al, 2014Zhao et al, , 2016 and Airy beams (Vettenburg et al, 2014) for LSFM, shown in Figure 5. Bessel beams are the most used as they are fairly easy to implement.…”
Section: Engineered Light Sheetsmentioning
confidence: 99%
See 3 more Smart Citations
“…As such it is of interest to look into nondiffracting, propagation-invariant beams. Various reports have emerged over the past few years evaluating Bessel beams (Andilla et al, 2017;Fahrbach, Gurchenkov, Alessandri, Nassoy, & Rohrbach, 2013b;Fahrbach & Rohrbach, 2010Gao, Shao, Chen, & Betzig, 2014;Gohn-Kreuz & Rohrbach, 2016;Zhang, Phipps, Goodwin, & Werner, 2016;Zhao et al, 2014Zhao et al, , 2016 and Airy beams (Vettenburg et al, 2014) for LSFM, shown in Figure 5. Bessel beams are the most used as they are fairly easy to implement.…”
Section: Engineered Light Sheetsmentioning
confidence: 99%
“…Reportedly, a major advantage is the acquisition speed, that ranges between 200 to 1,000 planes/s in dithered mode, which is one order of magnitude more than with classic Bessel beams. The technique is undoubtedly very effective, but the set-up is quite complex and the use of a SLM reduces the temporal resolution when multicolor imaging is required since the SLM must be rapidly switched and synchronized with every color change (Zhao et al, 2016). The solution proposed by Zhao and coworkers (Zhao et al, 2016) is to use a combination of "nonelectronic" optical components to create ultrathin Bessel sheets of the same thickness regardless of the input laser light, as long as it is in the visible range.…”
Section: Engineered Light Sheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, fluorescence intermittency (intensity blinking) is a common property of fluorophores, which has been used as an effective tool to break the optical diffraction limit. Super-resolution Optical Fluctuation Imaging (SOFI) is a super-resolution technique that achieves diffraction-unlimited imaging in all three dimensions through high-order cumulant analysis on the image sequence of intensity blinking fluorophores (Dertinger et al, 2009;Dertinger et al, 2010;Geissbuehler et al, 2012;Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%